Actin-Dependent and -Independent Functions of Cortical Microtubules in the Differentiation of Arabidopsis Leaf Trichomes. Issue 4 (8th April 2014) - Sambade, Adrian; Findlay, Kim; Schäffner, Anton R.; Lloyd, Clive W.; Buschmann, Henrik
Abstract : This investigation shows that genetic interactions of microtubule function in Arabidopsis trichome differentiation involve ANGUSTIFOLIA1 and F-actin. Detailed analyses of the cytoskeleton of growing trichomes in tortifolia2 distorted1 double mutants indicated that F-actin enhances microtubule dynamics and enables reorientation. Abstract: Arabidopsis thaliana tortifolía2 carries a point mutation in α-tubulin 4 and shows aberrant cortical microtubule dynamics. The microtubule defect of tortifolia2 leads to overbranching and right-handed helical growth in the single-celled leaf trichomes. Here, we use tortifolia2 to further our understanding of microtubules in plant cell differentiation. Trichomes at the branching stage show an apical ring of cortical microtubules, and our analyses support that this ring is involved in marking the prospective branch site. tortifolia2 showed ectopic microtubule bundles at this stage, consistent with a function for microtubules in selecting new branch sites. Overbranching of tortifolia2 required the C-terminal binding protein/brefeldin A-ADP ribosylated substrate protein ANGUSTIFOLIA1, and our results indicate that the angustifolia1 mutant is hypersensitive to alterations in microtubule dynamics. To analyze whether actin and microtubules cooperate in the trichome cell expansion process, we generated double mutants of tortifolia2 with distorted1, a mutant that is defective in the actin-related ARP2/3 complex. The double mutant trichomes showed a complete loss of growth anisotropy, suggesting a genetic interaction of actin and microtubules. Green fluorescent protein labeling of F-actin or microtubules in tortifolia2 distorted1 double mutants indicated that F-actin enhances microtubule dynamics and enables reorientation. Together, our results suggest actin-dependent and -independent functions of cortical microtubules in trichome differentiation.